50. CURRENT STATUS OF PUBLIC KNOWLEDGE ABOUT FAMILY MEDICINE IN THAI NGUYEN CITY AND ITS ASSOCIATED FACTORS IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status and associated factors influencing the knowledge of family medicine among the population of Thai Nguyen city in 2024.Method: From January 2024 to December 2024, 425 residents of Thai Nguyen city were the subject of a cross-sectional study design.Results: Women made up 60.2% of the study participants, with an average age of 56.7 ± 18.7 years. Seventy-six percent had an educational level above high school. Only 8.2% of the study participants had good general knowledge of family medicine; the remaining individuals had poor knowledge. No subject received information from medical staff; the Internet is the most popular source of information access (80.4%). Education level and information sources from newspapers, the Internet, television, friends and family are factors that are associated with the subject’s understanding of family medicine (p < 0.05).Conclusion: Understanding family medicine is crucial and requires consideration since it influences the capacity to create and implement the family medicine model in Vietnam.Keywords: Family medicine, general practitioner, knowledge.
Keywords: Family medicine; general practitioner; knowledge